Multichannel retailing and price competition. (1st June 2020) - Karray, Salma; Sigué, Simon Pierre
Abstract: We investigate the profitability of multichannel retailing for competing offline retailers. Each firm can sell a product both offline and online in a position of a first mover or follower in the online market. We find that, depending on the online market size and price competition levels across channels and retailers, the adoption of multichannel retailing may or may not enhance an offline retailer's profits in the first‐mover position. If one retailer profitably expands online, the second can also improve its profit by introducing another online channel to the detriment of the pioneer. However, when offline retailers are given the possibility of selecting an equilibrium channel mix, multichannel retailing could be adopted strategically by the two retailers to maintain their market shares, resulting in a prisoner's dilemma situation. In such a context, it drives down retail prices, increases sales, and reduces the profits of the two competing retailers.